Trustworthy distributed systems through integrity−reporting (invited book chapter) - Huh, J; Martin, A (2010)
With the growing influence of e-Science, substantial quantities of research are being facilitated, recorded, and reported by means of distributed computing. As a result, the scope for malicious intervention continues to grow, and so do the rewards available to those able to steal the models and data that have significant commercial value. Researchers are often reluctant to exploit the full benefits of distributed computing because they fear the compromise of their sensitive data or the uncertainty of the returned results. In this chapter, we propose two types of trustworthy distributed systems – one suitable for a computational system and the other for a distributed data system. Central to these systems is the novel idea of configuration resolver, which, in both designs, is responsible for filtering trustworthy hosts and ensuring that jobs are dispatched to those considered trustworthy. Furthermore, the blind analysis server enables statistical analyses to be performed on sensitive raw data – collected from multiple sites – without disclosing it to anyone.